Resveratrol and the mitochondria: From triggering the intrinsic apoptotic pathway to inducing mitochondrial biogenesis, a mechanistic view - de Oliveira, Marcos Roberto; Nabavi, Seyed Fazel; Manayi, Azadeh; Daglia, Maria; Hajheydari, Zohreh; Nabavi, Seyed Mohammad (Biochimica et biophysica acta, 2016)
Mitochondria, the power plants of the cell, are known as a cross-road of different cellular signaling pathways. These cytoplasmic double-membraned organelles play a pivotal role in energy metabolism and regulate calcium flux in the cells. It is well known that mitochondrial dysfunction is associated with different diseases such as neurodegeneration and cancer. A growing body of literature has shown that polyphenolic compounds exert direct effects on mitochondrial ultra-structure and function. Resveratrol is known as one of the most common bioactive constituents of red wine, which improves mitochondrial functions under in vitro and in vivo conditions. This paper aims to review the molecular pathways underlying the beneficial effects of resveratrol on mitochondrial structure and functions. In addition, we discuss the chemistry and main sources of resveratrol. Resveratrol represents the promising effects on mitochondria in different experimental models. However, there are several reports on the detrimental effects elicited by resveratrol on mitochondria. An understanding of the chemistry and source of resveratrol, its bioavailability and the promising effects on mitochondria brings a new hope to therapy of mitochondrial dysfunction-related diseases. •Resveratrol induces both pro-oxidant and antioxidant effects on mitochondria.•Resveratrol triggers redox and mitochondria-dependent cell death.•Resveratrol exerts antioxidant effects on mitochondria through Mn-SOD upregulation.•Resveratrol elicits mitochondrial biogenesis through multiple mechanisms.•The beneficial effects of resveratrol include increases in mitochondrial quality.